Efektivitas terapi bekam terhadap kadar kolesterol - zulkarnaini zul; Nona Rosalina; Daufi Saputra (Indonesia, 2019)
The development of science and technology has caused various lifestyle changes, one of which is fast food that contains high cholesterol. Based on a 2002 World Health Organization report, 4.4 million deaths were due to hypercholesterolemia or 7.9% of the total deaths. Management of hypercholesterolemia includes pharmacological therapy and non-pharmacological therapy, one of which is cupping therapy. This study aims to determine the effectiveness of cupping therapy on cholesterol levels in Blang Pulo Village, Muara Satu District, Lhokseumawe City. This research is a quasy experiment using a one group pretest and posttest research design. Sampling technique with quota sampling, totaling 30 respondents. Data collection tools in the form of observation sheets and digital measuring devices for cholesterol levels. The results showed the average cholesterol level on Pretest  was 299.4 mg/dl and Posttest was 213.0 mg/dl. Differences in average cholesterol levels of 86.4 mg/dl. Paired t-test results obtained p value>0.05, meaning that there are differences in cholesterol levels on prestest and posttest, in conclusion cupping therapy is effective against reducing cholesterol levels in patients with hypercholesterolemia in Blang Pulo Village, Muara Satu District, Lhokseumawe City. It is recommended for health workers, in addition to providing pharmacological therapy, but also applying nonpharmacological therapy such as cupping therapy in patients with hypercholesterolemia.